STUDI PEMANFAATAN ROTAN OLEH MASYARAKAT SETEMPAT PADA KAWASAN HUTAN DI DESA KASROMEGO KECAMATAN BEDUAI KABUPATEN SANGGAU - Gusniati, .; Zainal, Sofyan; Fahrizal, . (Universitas Tanjungpura, 2017)
Rattan is a source of biological in Indonesia and usually referred to as a potential non-timber for forest products (NTFP). This research aims to determine the species of rattan used by the people in Kasromego village of Beduai Subdistrict, Sanggau regency, and the processing of each species of rattan and parts used by the community. The method used was descriptive analysis with a qualitative approach. The qualitative approach in this study is to provide a description of the data events based on facts with direct interview techniques with a number of respondents to obtain answers. Sampling was done through snowball sampling method. The results of the study show that the villagers of Kasremego take advantage of as many as 7 species of rattan, namely: saga ( Calamus caesius Blume ), marau ( Karthalsia rigida Blume ), halus ( Karthalsia perox Becc ), irit ( Calamus trachycoleus Becc), semut ( Korthalsia sescaphigera Mart ), sanjat ( Calamus paspalantus Becc ) and samere ( Plectomiopsis mira J. Dransf ) As for the parts of rattan used are for the semut rattan, the innermost frond is used for food of vegetables. Tha rattan used to make ropes is the halus rattan, the part of this rattan used is the trunk. For customary/religious ceremonies, typically the people used the halus rattan, and the part of rattan used is the leaf. Keywords: Rattan, research method, rattan species